#### Answer

Vertex = (-1, -3)

#### Work Step by Step

x = $y^{2}$ + 6y + 8
x = $(y+3)^{2}$ - 9 + 8
x = $(y+3)^{2}$ - 1
Thus vertex = (-1, -3)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

Vertex = (-1, -3)

x = $y^{2}$ + 6y + 8
x = $(y+3)^{2}$ - 9 + 8
x = $(y+3)^{2}$ - 1
Thus vertex = (-1, -3)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.